Near-field coupling and resonant cavity modes in plasmonic nanorod metamaterials. (8th September 2016) - Song, Haojie; Zhang, Junxi; Fei, Guangtao; Wang, Junfeng; Jiang, Kang; Wang, Pei; Lu, Yonghua; Iorsh, Ivan; Xu, Wei; Jia, Junhui; Zhang, Lide; Kivshar, Yuri S; et al.
Abstract: Plasmonic resonant cavities are capable of confining light at the nanoscale, resulting in both enhanced local electromagnetic fields and lower mode volumes. However, conventional plasmonic resonant cavities possess large Ohmic losses at metal-dielectric interfaces. Plasmonic near-field coupling plays a key role in a design of photonic components based on the resonant cavities because of the possibility to reduce losses. Here, we study the plasmonic near-field coupling in the silver nanorod metamaterials treated as resonant nanostructured optical cavities. Reflectance measurements reveal the existence of multiple resonance modes of the nanorod metamaterials, which is consistent with our theoretical analysis. Furthermore, our numerical simulations show that the electric field at the longitudinal resonances forms standing waves in the nanocavities due to the near-field coupling between the adjacent nanorods, and a new hybrid mode emerges due to a coupling between nanorods and a gold-film substrate. We demonstrate that this coupling can be controlled by changing the gap between the silver nanorod array and gold substrate.